2003
DOI: 10.1016/s0257-8972(02)00617-5
|View full text |Cite
|
Sign up to set email alerts
|

Frictional behavior of diamondlike carbon films in vacuum and under varying water vapor pressure

Abstract: In this study, we investigated the frictional behavior of both hydrogenated and hydrogen-free diamondlike carbon (DLC) films in high vacuum (10 -6 Pa) at room temperature. Water was also introduced into the vacuum chamber to elucidate its effects on DLC film tribology. The hydrogen-free DLC (also referred to as tetrahedral amorphous carbon, or ta-C) was produced by an arc-PVD process, and the highly hydrogenated DLC was produced by plasma-enhanced chemical-vapor deposition.Tribological measurements of these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
109
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 16 publications
11
109
0
Order By: Relevance
“…The hydrogen passivation mechanism of Erdemir [25,26] is replaced by the preferential adsorption of the most polar molecules onto the DLC surface [45], and as a consequence the friction is controlled by the molecular species at the interface as opposed to the hydrogen content of the coating. In addition, a non-hydrogenated DLC coating that shows a high coefficient of friction in an inert environment may provide a similar coefficient of friction to that of a hydrogenated coating in water [46]. Table 2 outlined the approximate range for the coefficient of friction in varying humidity and in water for a-C, a-C:H, and ta-C coatings.…”
Section: Friction In a Water Environmentmentioning
confidence: 99%
“…The hydrogen passivation mechanism of Erdemir [25,26] is replaced by the preferential adsorption of the most polar molecules onto the DLC surface [45], and as a consequence the friction is controlled by the molecular species at the interface as opposed to the hydrogen content of the coating. In addition, a non-hydrogenated DLC coating that shows a high coefficient of friction in an inert environment may provide a similar coefficient of friction to that of a hydrogenated coating in water [46]. Table 2 outlined the approximate range for the coefficient of friction in varying humidity and in water for a-C, a-C:H, and ta-C coatings.…”
Section: Friction In a Water Environmentmentioning
confidence: 99%
“…This is hypothesized to reduce friction and wear by preventing carboncarbon bonding across the sliding interface. For example, in an environment containing water or hydrogen, self-mated friction coefficients can be as low as ~0.07 for ta-C, 22 and ~0.005 for UNCD, 19 while in inert atmospheres (e.g., highly pure nitrogen or argon gas) or vacuum, the friction coefficients for both materials increase by one to two orders of magnitude. 13,19,22 Matta et al performed self-mated pin-on-disk studies with H-free amorphous carbon (a-C) and ta-C coated on ruby and sapphire substrates in an H 2 environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an environment containing water or hydrogen, self-mated friction coefficients can be as low as ~0.07 for ta-C, 22 and ~0.005 for UNCD, 19 while in inert atmospheres (e.g., highly pure nitrogen or argon gas) or vacuum, the friction coefficients for both materials increase by one to two orders of magnitude. 13,19,22 Matta et al performed self-mated pin-on-disk studies with H-free amorphous carbon (a-C) and ta-C coated on ruby and sapphire substrates in an H 2 environment. 12 The ta-C film in this study was grown by cathodic arc deposition, had a Young's modulus of ~650 GPa, and is mentioned to have more sp 3 -bonded carbon than the a-C films grown by sputter-ion deposition (Young's modulus ~250 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proved that the presence of hydrogen, oxygen and other environmental species in diamond-like carbon (DLC) testing environments affects the tribological behaviour of DLC wear in water [1][2][3][4][5][6][7]. The hydrogen content of DLC coatings shows low friction in inert environments due to very low adhesive forces between the fully hydrogen-terminated sliding surfaces of these carbon coatings which, as proposed by Erdemir [1,3], are not applicable when DLC slides in a water environment.…”
Section: Introductionmentioning
confidence: 99%
“…Andersson et al reported that the friction of hydrogenated DLC under varying water pressure is controlled by the water molecules that are adsorbed onto the DLC surfaces, which could change the interaction to a dipole-like one, increasing the adhesive forces and hence, the friction [5]. Studies conducted by J. Anderson et al in a high vacuum environment with various added gases also found that the presence of oxygen molecules slightly increased the friction coefficient of hydrogenated carbon films as compared to that in the hydrogen-free DLC [2], indicating the sensitivity of hydrogenated DLC to water and oxygen.…”
Section: Introductionmentioning
confidence: 99%